1993
DOI: 10.1177/155005949302400110
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Coma Due to Acute Basilar Artery Migraine: Correlation of EEG and Brainstem Auditory Evoked Potential Patterns

Abstract: Our patient presented with three episodes of deep coma in 5 weeks, followed by a complete recovery. The neuroradiological tests and spinal fluid analysis excluded structural lesions, including subarachnoid hemorrhage, from the diagnosis. A nonconvulsive status was excluded by 24-hour EEG monitoring. The EEGs and brainstem auditory evoked responses were abnormal during ictus, but they reversed to normal with the clinical recovery. Timely neurophysiological tests helped in the diagnosis of basilar artery migrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Potentially, release of these substances could lead to a functional vestibular tone imbalance due to asymmetric activation or deactivation of vestibular neuronal activity. Transient and persisting brainstem dysfunction has been documented with brainstem auditory evoked potentials and positron emission tomography in migraine sufferers [60][61][62].…”
Section: Pathophysiologymentioning
confidence: 98%
“…Potentially, release of these substances could lead to a functional vestibular tone imbalance due to asymmetric activation or deactivation of vestibular neuronal activity. Transient and persisting brainstem dysfunction has been documented with brainstem auditory evoked potentials and positron emission tomography in migraine sufferers [60][61][62].…”
Section: Pathophysiologymentioning
confidence: 98%
“…While some authors observed no abnormalities in brainstem responses [23,25,28], others have described some alterations of brainstem functions in migrainours [7,26,27,[29][30][31]. In this study, we aimed to document if any hearing changes were present in children suffering from migraine during or/and between migraine attacks.…”
mentioning
confidence: 95%
“…I-V and III-V IPLs were significantly prolonged but not exceed clinical norm Ganji et al [27] A case A basilar artery migraine patient At migraine attack ABR were abnormal during ictus, but they reversed to normal with the clinical recovery Ganji [28] A Drake et al [26] found peak latency and interpeak latency differences in 50 patients. As mentioned above these differences may explain the contradictory results.…”
mentioning
confidence: 97%
See 2 more Smart Citations